Type-specific incidence, clearance and predictors of cervical human papillomavirus infections (HPV) among young women: a prospective study in Uganda - Banura, Cecily; Sandin, Sven; van Doorn, Leen-Jan; Quint, Wim; Kleter, Bernhard; Wabwire-Mangen, Fred; K Mbidde, Edward; Weiderpass, Elisabete (Infectious Agents and Cancer, 2010)
While infections with human papillomavirus (HPV) are highly prevalent among sexually active young women in Uganda, information on incidence, clearance and their associated risk factors is sparse. To estimate the incidence, prevalence and determinants of HPV infections, we conducted a prospective follow-up study among 1,275 women aged 12-24 years at the time of recruitment. Women answered a questionnaire and underwent a pelvic examination at each visit to collect exfoliated cervical cells. The presence of 42 HPV types was evaluated in exfoliated cervical cells by a polymerase chain based (PCR) assay (SPF10-DEIA LiPA).
Keywords: cervical; Human Papillomavirus Infections (HPV); Young women